Fabricating SiO2-coated V2O5 nanoflake arrays for high-performance lithium-ion batteries with enhanced cycling capability. Issue 11 (23rd February 2016) - Xu, Haitao; Chen, Jida; Zhang, Huijuan; Zhang, Yan; Li, Wenxiang; Wang, Yu
Abstract : SiO2 -coated V2 O5 nanoflake arrays were designedly fabricated to substantially enhance the overall lithium-ion battery cycling performance. Abstract : In the designed synthesis, hierarchical V2 O5 nanoflake arrays were prepared via calcining NH4 VO3 arrays. Then V2 O5 arrays were coated with a porous SiO2 layer. Finally, a unique pattern of SiO2 -coated V2 O5 nanoflake arrays was obtained for the first time. This hierarchical and elaborate architecture possessed several impressive virtues, including a large surface-to-volume ratio, short diffusion paths of lithium ions, and strong physical adhesion between the current collector and active material. When acting as a binder-free electrode for lithium-ion batteries, the electrode exhibited a high capacity and good rate capability. At a current density of 0.1 A g −1, a high capacity of 289 mA h g −1 was obtained, and even at a high current rate of 4 A g −1, a capacity of 175 mA h g −1 could be still maintained. Remarkably, the hierarchical nanostructures sharply improved the cycling stability of the binder-free V2 O5 electrode. As a result, a high reversible capacity of 256 mA h g −1 is obtained after 500 cycles.